Deep brain stimulation in the internal capsule and nucleus accumbens region: responses observed during active and sham programming. Issue 3 (29th September 2006) - Okun, Michael S; Mann, Giselle; Foote, Kelly D; Shapira, Nathan A; Bowers, Dawn; Springer, Utaka; Knight, William; Martin, Pamela; Goodman, Wayne K
Abstract : Background: Recently, anterior limb of the internal capsule and nucleus accumbens deep brain stimulation (DBS) has been used in the treatment of medication-refractory obsessive–compulsive disorder (OCD). This region has been previously explored with lesion therapy, but with the advent of DBS there exists the possibility of monitoring the acute and chronic effects of electrical stimulation. The stimulation-induced benefits and side effects can be reversibly and blindly applied to a variety of locations in this region. Objective: To explore the acute effects of DBS in the anterior limb of the internal capsule and nucleus accumbens region. Methods: Ten total DBS leads in five patients with chronic and severe treatment-refractory OCD were tested. Patients were examined 30 days after DBS placement and received either "sham" testing or actual testing of the acute effects of DBS (the alternative condition tested 30 days later). Results: Pooled responses were reviewed for comparability of distribution using standard descriptive methods, and relationships between the variables of interest were sought using χ 2 analysis. A total of 845 stimulation trials across the five patients were recorded and pooled. Of these 16% were elicited from sham stimulation and 17% from placebo (0 V stimulation). A comparison of active to sham trials showed that sham stimulation was not associated with significant side effects or responses from patients. Non-mood-related responses were found to be significantly associated with the ventral lead contacts (0 and 1) (p = 0.001). Responses such as taste, smell and smile were strongly associated with the most ventral lead positions. Similarly, physiological responses—for example, autonomic changes, increased breathing rate, sweating, nausea, cold sensation, heat sensation, fear, panic and panic episodes—were significantly associated with ventral stimulation (p = 0.001). Fear and panic responses appeared clustered around the most ventral electrode (0). Acute stimulation resulted in either improved or worsened mood responses in both the dorsal and ventral regions of the anterior limb of the internal capsule. Conclusion: The acute effects of DBS in the region of the anterior limb of the internal capsule and nucleus accumbens, particularly when obtained in a blinded fashion, provide a unique opportunity to localise brain regions and explore circuitry.